Study of Herbal Toothpaste Made from Virgin Coconut Oil and Gambier (Uncaria gambir Roxb) - Zaadah Zaadah; Novizar Nazir; Novelina Novelina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
The purpose of this study was to find out the effect of utilizing virgin coconut oil (VCO) and gambir (Uncaria gambir Roxb) in several combinations on the manufacture of herbal toothpaste on its characteristics and antibacterial activity. The research design used is a Completely Randomized Design (CRD) with five treatments and three repeats so that in this study 5 x 3 there were 15 combinations of treatments. The resulting research data is then analyzed using the F test and if the data differs is real then proceed with the Duncan News Multiple Range Test (DNMRT) tests to find out the 5% significance level between treatments. The determination of formulations in the manufacture of toothpaste using a concentration of 10% VCO as a toothpaste base refers to the previous research formula and the addition of 0.9%, 1.8%, 2.6%, 3.5%, and 4.3% of gambier. Based on research that has been done, it can be concluded that the addition of gambir concentrations has a real influence on the pH value and foam formation but does not affect homogeneity, hedonic values (color, aroma, taste, texture, and overall value) and the diameter of the bland zone against Streptococcus mutans bacteria. The best toothpaste preparation is treatment 3, which is the addition of 2.6% of the toothpaste base preparation with a pH value of 8.42, homogeneous, foam height of 10.70 mm, color preference (3.85), the aroma (4.25), flavor (3.30), texture (3.45), overall (3.80), strong indicator bland zone diameter (34.55 mm).